"The War Comes Home:" Recurring Themes in Contemporary Studies of the Southern Home Front During the American Civil War - Navarrete Quinto, Wilfred (The Toro Historical Review, 2025)
Within the last thirty years, American Civil War historians have identified the various ways in which the war impacted life on the Southern home front during the war. Drawing from the works of contemporary historians such as Stephen V. Ash and LeeAnn Whites, this paper delves into three themes that continuously emerged in their writings. More specifically, this paper explores civilian-centred conflicts, responses to Union presence, and the construction of the Lost Cause mythology as discussed by the likes of Ash, Whites, Lisa Tendrich Frank, Scott Reynolds Nelson, Carol Sheriff, Jonathan Dean Sarris, Daniel Sutherland, and Yael A. Sternhell. While the war witnessed Union and Confederate soldiers clashing head-on, civilians on the Southern home front waged their own battles against occupying forces and neighbours alike. Unlike soldiers, however, their fight to keep the Confederacy alive extended far beyond the war's end.